Amelioration of age-related cognitive decline and anxiety in mice by Centella asiatica extract varies by sex, dose and mode of administration - Gray, Nora E.; Hack, Wyatt; Brandes, Mikah S.; Zweig, Jonathan A.; Yang, Liping; Marney, Luke; Choi, Jaewoo; Magana, Armando Alcazar; Cerruti, Natasha; McFerrin, Janis; Koike, Seiji; Nguyen, Thuan; et al. (Frontiers in Aging, 2024)
A water extract (CAW) of the Ayurvedic plant Centella asiatica administered in drinking water has been shown to improve cognitive deficits in mouse models of aging and neurodegenerative diseases.Here the effects of CAW administered in drinking water or the diet on cognition, measures of anxiety and depression-like behavior in healthy aged mice are compared.Three-and eighteen-month-old male and female C57BL6 mice were administered rodent AIN-93M diet containing CAW (0, 0.2, 0.5 or 1% w/w) to provide 0, 200 mg/kg/d, 500 mg/kg/d or 1000 mg/kg/d for a total of 5 weeks. An additional group of eighteen-month-old mice were treated with CAW (10 mg/mL) in their drinking water for a total of five weeks to deliver the same exposure of CAW as the highest dietary dose (1000 mg/kg/d). CAW doses delivered were calculated based on food and water consumption measured in previous experiments. In the fourth and fifth weeks, mice underwent behavioral testing of cognition, anxiety and depression (n=12 of each sex per treatment group in each test).Aged mice of both sexes showed cognitive deficits relative to young mice while only female aged mice showed increased anxiety compared to the young female mice and no differences in depression were observed between the different ages. CAW (1000 mg/kg/d) in the drinking water improved deficits in aged mice in learning, executive function and recognition memory in both sexes and attenuated the increased measures of anxiety observed in the aged female mice. However, CAW in the diet only improved executive function in aged mice at the highest dose (1000 mg/kg/d) in both sexes and did so less robustly than when given in the water. There were no effects of CAW on depression-like behavior in aged animals regardless of whether it was administered in the diet or the water.These results suggest that CAW can ameliorate age-related changes in measures of anxiety and cognition and that the mode of administration is important for the effects of CAW on resilience to these age-related changes.